2023
DOI: 10.1108/jeim-06-2022-0219
|View full text |Cite
|
Sign up to set email alerts
|

The effect of IoT capability on supply chain integration and firm performance: an empirical study in the UK retail industry

Abstract: PurposeThe purpose of this study is to use empirical data to examine the hierarchical impact of the Internet of things capability on supply chain integration (SCI), supply chain capability (SCC) and firm performance (FP) in the UK retail industry.Design/methodology/approachA deductive approach was employed to carry out this research. Structural equation modelling (SEM) was performed using the partial least square method (SmartPLS 3.3.3) to test theoretical predictions which underlie the relationships among Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 114 publications
1
6
0
Order By: Relevance
“…Many researchers have developed an opinion that LC has the potential to enhance resilience and enhance sustainability and performance [69]. Our finding also supports the arguments of Argyropoulou et al [40], which explain that LC can integrate various supply chain processes, including logistics, packaging, distribution, warehousing, return functions, order management, and monitoring. It also facilitates real-time information sharing among multiple members of a SC.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Many researchers have developed an opinion that LC has the potential to enhance resilience and enhance sustainability and performance [69]. Our finding also supports the arguments of Argyropoulou et al [40], which explain that LC can integrate various supply chain processes, including logistics, packaging, distribution, warehousing, return functions, order management, and monitoring. It also facilitates real-time information sharing among multiple members of a SC.…”
Section: Discussionsupporting
confidence: 88%
“…It also facilitates real-time information sharing among multiple members of a SC. This results in real-time visibility into supply chain operations, leading to improved overall firm performance [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it enhances the efficiency of material flow, offers operational flexibility , streamlines financial processes, and enhances communication among individuals involved. In their study Argyropoulou et al (2023) examined the integration of IT platforms inside organizational supply chains, encompassing several factors such as strategic supplier partnerships, customer relationships, and ICT. The present study formulated the following hypotheses to examine the impact of the SCP (Strategic supplier partnership and customer relationship) on the ICT in the Jordanian pharmaceutical Sector: H3: Strategic supplier partnership has significant effect on the ICT in the Jordanian pharmaceutical Sector.…”
Section: Scm and Ictmentioning
confidence: 99%
“…In the process, they leverage digital technology to restructure the processes, coordination, organization and value of business in both the external and internal organization of supply chains, which is what DSC means [28]. Based on the theories of resource-based and dynamic capabilities [29,30], and applying various methods, which have included case studies, QCA, DID and questionnaire survey, scholars found the partial effects of DSC on enterprises, such as competitive advantage [31,32], supply chain management modeling and supply chain efficiency [25,33]. Due to the lack of empirical measurements for DSC, few studies could offer empirical evidence for the effects of DSC [34,35].…”
Section: Introductionmentioning
confidence: 99%